A Metagenomics Investigation of Carbohydrate-Active Enzymes along the Gastrointestinal Tract of Saudi Sheep - Al-Masaudi, Saad; El Kaoutari, Abdessamad; Drula, Elodie; Al-Mehdar, Hussein; Redwan, Elrashdy M.; Lombard, Vincent; Henrissat, Bernard (Frontiers in Microbiology, 2017)
The digestive microbiota of humans and of a wide range of animals has recently become amenable to in-depth studies due to the emergence of DNA-based metagenomic techniques that do not require cultivation of gut microbes. These techniques are now commonly used to explore the feces of humans and animals under the assumption that such samples are faithful proxies for the intestinal microbiota. Sheep (Ovis aries) are ruminant animals particularly adapted to life in arid regions and in particular Najdi, Noaimi (Awassi) and Harrei (Harri) breeds that are raised in Saudi Arabia for milk and/or meat production. Here we report a metagenomics investigation of the distal digestive tract of one animal from each breed that (i) examines the microbiota at three intestinal subsites (small intestine, mid-colon and rectum), (ii) performs an in-depth analysis of the carbohydrate-active enzymes genes encoded by the microbiota at the three subsites and (iii) compares the microbiota and carbohydrate-active enzyme profile at the three subsites across the different breeds. For all animals we found that the small intestine is characterized by a lower taxonomic diversity than that of the large intestine and of the rectal samples. Mirroring this observation, we also find that the spectrum of encoded carbohydrate-active enzymes of the mid-colon and rectal sites is much richer than that of the small intestine. However, the number of encoded cellulases and xylanases in the various intestinal subsites was found to be surprisingly low, indicating that the bulk of the fiber digestion is performed upstream in the rumen, and that the carbon source for the intestinal flora is probably constituted of the rumen fungi and bacteria that pass in the intestines. In consequence we argue that ruminant feces, which are often analyzed for the search of microbial genes involved in plant cell wall degradation, are probably a poor proxy for the lignocellulolytic potential of the host.